2017
DOI: 10.1038/nature22819
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 prepares brown adipose tissue for acute thermogenic challenge

Abstract: Brown adipose tissue (BAT) is a thermogenic organ that dissipates chemical energy as heat to protect animals against hypothermia and to counteract metabolic disease1. However, the transcriptional mechanisms that determine BAT thermogenic capacity prior to environmental cold are unknown. Here we show that Histone Deacetylase 3 (HDAC3) is required to activate BAT enhancers to ensure thermogenic aptitude. Mice with BAT-specific genetic ablation of HDAC3 become severely hypothermic and succumb to acute cold exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
168
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 58 publications
6
168
1
1
Order By: Relevance
“…Accordingly, our study clarifies the outcome of WAT browning in HDAC3 deficient mice might be because it has the same effect of HDAC3 suppression originated from β-AR stimulation to regulate Ucp1 expression. Interestingly, the other study showed that the ablation of HDAC3 in mice during cold exposure (4 °C, 24 h) failed to activate the thermogenesis program in BAT [37]. In contrast, this study suggests a positive regulation of HDAC3 to browning.…”
Section: Discussioncontrasting
confidence: 53%
“…Accordingly, our study clarifies the outcome of WAT browning in HDAC3 deficient mice might be because it has the same effect of HDAC3 suppression originated from β-AR stimulation to regulate Ucp1 expression. Interestingly, the other study showed that the ablation of HDAC3 in mice during cold exposure (4 °C, 24 h) failed to activate the thermogenesis program in BAT [37]. In contrast, this study suggests a positive regulation of HDAC3 to browning.…”
Section: Discussioncontrasting
confidence: 53%
“…A complementary story was recently published identifying a role for HDAC3 in establishing a transcriptional landscape in BAT required for the rapid response to acute cold challenge (Emmett et al, 2017). Dating mining of RNA-seq from HDAC3 KO BAT (Emmett et al, 2017) and comparison with RNA-seq from ERRγKO BAT (both performed at TN) revealed commonly downregulated genes in HDAC3KO and ERRγKO BAT, including the key genes UCP1 and Cox7a1, raising the logical possibility of cooperation between HDAC3 and ERRγ in BAT (Figure S2F).…”
Section: Resultsmentioning
confidence: 99%
“…Dating mining of RNA-seq from HDAC3 KO BAT (Emmett et al, 2017) and comparison with RNA-seq from ERRγKO BAT (both performed at TN) revealed commonly downregulated genes in HDAC3KO and ERRγKO BAT, including the key genes UCP1 and Cox7a1, raising the logical possibility of cooperation between HDAC3 and ERRγ in BAT (Figure S2F). However, the majority of the downregulated genes were unique to the specific model, consistent with predominantly parallel and possibility complementary regulatory pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, this trade-off between thermogenic capacity and overall organismal fitness is due to the specific reduction of mtDNA-encoded gene expression in the BAT (Figure 7). In contrast, reducing Pgc1α-mediated mitochondrial biogenesis in brown-adipocyte-specific Irf4 and Hdac3 knockout mice affected the expression of both mtDNA- and nuclear-encoded genes in BAT, leading to thermogenic defects but without metabolic benefits (Emmett et al, 2017; Kong et al, 2014). Tfam BKO mice are resistant to long-term HFD-induced insulin resistance, dyslipidemia, and non-alcoholic fatty liver disease, which might be secondary to reduced adiposity.…”
Section: Discussionmentioning
confidence: 97%